A new species of Schizachyrium (Poaceae: Andropogoneae) from Brazil - Peichoto, Myriam Carolina (2006)
A new Brazilian species, Schizachyrium hatschbachii Peichoto is described and illustrated. It is restricted to southern Brazil, where it grows in grasslands. Diagnostic characters, description, detailed illustration and taxonomic comments are given. Its relationships with S. gracilipes and S. microstachyum ssp.elongatum are discussed.